ANALISA LITERASI KEUANGAN DAN PERAN GENERASI Z DALAM MENYOKONG CASHLESS SOCIETY DI INDONESIA - Wening Purbatin Palupi Soenjoto (Reinforce: Journal of Sharia Management, 2023)
Post the COVID-19 pandemic, it is undeniable that online spending has changed shopping behavior patterns by employing non-cash payment methods. During the COVID-19 pandemic, the use of non-cash payments was significantly encouraged due to restrictions on public activities, as cash was considered a potential medium for the transmission of the COVID-19 virus. This research explores the phenomenon of using cash as a consequence of the COVID-19 pandemic and whether it has led to an increase in non-cash financial literacy. It also investigates whether government programs aimed at promoting non-cash transactions can foster a non-cash society as a means of enhancing the effectiveness of non-cash transactions or if they instead promote consumptive behavior due to a lack of understanding of non-cash financial literacy. The research employs a qualitative phenomenological method, involving interviews with 50 respondents aged 19-21 years. Additionally, interviews were conducted with two employees from Bank BSI Jombang and BRI Pulung Ponorogo to gather information related to banking. The study aims to reveal the impact of COVID-19 on the increased use of cashless products among Generation Z and describe the relationship between digital literacy skills and their influence on consumptive behavior among young individuals. The research findings suggest that cashless users aged 19-21 years influence consumptive behavior, but their knowledge of digital financial literacy is lacking. They primarily use non-cash methods for online shopping transactions, and their digital financial literacy is limited to debit and credit functions within bank account transactions. The results indicate that the 50 respondents have limited understanding of non-cash financial literacy, and non-cash payment products are primarily used for online shopping and sometimes mismanagement of financial resources.